Electronic structure and magnetic properties of dilute Fe alloys with transition-metal impurities - B. Drittler; N. Stefanou; S. Blügel; R. Zeller; P.H. Dederichs (Physical Review B, 1989)
We present ab initio calculations for dilute Fe alloys with 3d and 4d elements. The calculations are based on local-density approximation of density-functional theory and employ the Korringa-Kohn-Rostoker Green’s-function method. Results are given for the densities of states, the local moments, and the magnetization oscillations around the impurities. A detailed comparison is made with measurements of the electronic specific heat, with neutron-scattering results for the moments of the impurity and the neighboring host atoms, and with magnetization measurements. Contrary to the case of Co and Ni alloys, the majority-spin band contributes most to the screening in the Fe alloys. This arises from the fact that the Fermi energy falls into the minimum of the minority-spin density of states. The results are in qualitative agreement with a proposed pseudogap theory and naturally explain why Fe alloys show such a complicated magnetic behavior.